# How do you solve #sqrt(2x+10)-2sqrtx=0#?

##### 2 Answers

#### Answer:

#### Explanation:

Add

Square both sides:

Subtract

#### Answer:

#### Explanation:

First get

#sqrt(2x+10) cancel(- 2sqrtx + 2sqrtx) = 0 + 2sqrtx# - use additive inverse

#sqrt(2x+10) = 2sqrtx#

Now square both sides. Remember that squaring a square root is equal to that number under the square root.

#(sqrt(2x+10))^2 = (2sqrtx)^2# - square each side, because what you do to one side, you must do to the other

#2x+10 = 2^2 * (sqrt(x))^2# - Follow this concept:[#(ab)^x = a^x * b^x# ]

#2x+10 = 4x#

Now we can isolate the variable and identify

#cancel(2x-2x) + 10 = 4x-2x# - use additive inverse

#10 = 2x# - combine like terms

#10/2 = (cancel(2)x)/(cancel(2))# - divide by two

**Final Answer:**

#color(blue)(5 = x)#